A Study Of Meaning In Al Mahsar's Song Lyrics "Pangeran Inaq": Semiotic Riffaterre Analysis - Syamsurrijal, Syamsurrijal; Hadi, M. Zaki Pahrul; Miswaty, Titik Ceriyani (Jurnal Ilmiah Mandala Education (JIME), 2023)
Song is an aesthetic expression of the soul through words. Songs can also be interpreted as literary works because of the beauty of the words used in each verse. Song has two main building structures, namely, an inner structure and a physical structure. In addition, in a song, there are several markers, both in the form of meanings that need to be translated by the readers themselves and linguistic markers that do not require reinterpretation. The field of study that studies and examines signifiers, symbols, and signs is called semiotics. Semiotics is a scientific study that studies the signs that exist in a literary work. The purpose of this research is to find out the change of meaning in Pangeran Inaq's song, to find out the hypogran or background of the creation of Pangeran Inaq's song, to find out the hermeneutic reading of Pangeran Inaq's song, and to find out the creation of meaning in song. This research method uses a qualitative Pangeran Inaq's interpretive approach. The results of this research show that the replacement of meaning occurs in the first stanza of the first line and the third and fourth stanzas. The hypogram, or background, for the creation of this song, is a child who misses his mother's presence. To release his longing, he created this song. The result of a hermeneutic reading of this song is someone who is remembering all the love and kindness of his mother, who has passed away; he has never been separated from his mother; his sorrows and joys are always with his mother. The creation of meaning occurs because there is repetition in every stanza of the last line